Inovação de modelos de negócios para a sustentabilidade: a história da Braskem de transição de um modelo de negócio de economia linear para um modelo de economia circular - Beuter Júnior, Nelson (Universidade do Vale do Rio dos Sinos, 2020)
Innovating in business models for sustainability is the process of building solutions that create environmental, social and economic value, for the firm and its entire value chain. One of the possibilities for innovation is the transition from linear business models to circular business models. The understanding of how this process of transition from a linear to a circular business model occurs and evolves remains unknown. Through a single case study carried out with the Brazilian petrochemical company Braskem S.A., the process of transition from a linear to a circular business model was investigated, in light of the dynamic capabilities theory. Braskem, a commodities company with global operations, conceived in 2002 as a linear business model, began in recent years a process of transition to a circular business model. This case is a rare example, given that this type of business model transition is not common in this type of industry. It is also revealing, given that the entire history of the firm was explored, from a qualitative approach, with the application of procedural methodology. Interviews and secondary data were collected and analyzed using narrative, time scheduling, and visual maps. Four evolutionary phases of the business model innovation process for sustainability were identified: development, maturation, consolidation, and renewal of the value proposition. Each phase was associated with a different market differentiation strategy. It was found that the phase changes occurred because, over time, the exchange of differentiation strategies made the firm obtain a competitive advantage. The micro-foundations of dynamic capabilities that contributed to this innovation process were highlighted. A new dynamic capacity, called orchestrating, has been proposed. It is associated with the mobilization of resources external to the firm, to create value not only for itself but also for the other links in its value chain. Two micro-foundations of the transforming capacity (co-innovation and governance) and two of the orchestrating capacity (development of the value chain and influence on the value chain), presented themselves as essential for firms that are in transit from a linear model to a circular business model. A deepening of the sensing capacity (monitoring market demands), proved to be responsible for providing agility and market differentiation to the firm, which innovates in business models for sustainability.
Keywords: Inovação de modelos de negócio para a sustentabilidade; Economia circular; Capacidades dinâmicas; Transição; Microfundamentos; Sustainable business model innovation; Circular economy; Dynamic capabilities; Transition; Microfoundations; ACCNPQ::Ciências Sociais Aplicadas::Administração